Inquérito sobre a mediação parental do tempo de tela na primeira infância - Benevides, Jéssica Lima (2023)
The use of media devices, such as television, video games and devices such as tablets and smartphones, has been increasingly present in the daily life of the population, especially after the COVID-19 pandemic, including in the early years of childhood. This creates new challenges for parents, educators and health professionals in the world, including nursing, that mediates the use of screens by children and adolescents to reduce risks and enhance online opportunities. Parental mediation theory proposes that parents use different interpersonal communication strategies to mediate and mitigate the negative effects of using media devices on their children's lives. Three styles of parental mediation can be highlighted: the restrictive approach, followed by active mediation, with an instructive and/or regulatory character, and co-visualization. Based on the above, the study aimed to understand behaviors and habits related to screen use by children up to 5 years old and their caregivers during the COVID-19 pandemic. This is a cross sectional survey, with a cross-cultural adaptation stage of the “Parental Media Guidance Scale”. Data collection took place in June, July and August 2021, a period in which the state of Ceará was in strict social isolation due to the COVID-19 pandemic. Thus, the research scenario was virtual. The final sample consisted of 417 questionnaires returned by parents or legal guardians of children aged zero to five years. The following instruments were used: Sociodemographic and health questionnaire; Questionnaire on Family Use of Media Devices and “Parental Media Guidance Scale”, which were sent to subjects through a link. For the application of the questionnaire, the translation and cross-cultural adaptation of the “Parental Media Guidance Scale” was initially carried out. Data were tabulated, analyzed and displayed in tables and graphs. Tests used were: Pearson's chi-square and likelihood ratio. The ethical aspects were met, being approved by the COMEPE of UFC under CAAE 28201319.0.0000.5054. A significant association was found between instructive parental mediation styles (p=0,026) and co-vising (p<0,0001) and the age group of the children. As well as between the instructive parental mediation style and income (p=0,031) and the parents' marital status (p=0,04). There was still a significant association between the co-viewing style and the children's screen time and between the restrictive style and the parents' screen time. Regarding screen use habits, the devices most accessed by families were smartphones and smartTVs. The children's screen time showed a statistically significant association with the variables age group of the child (p=0,000), parents' marital status (p=0,017) and family income (p=0,018). Parents' screen time was significantly associated with marital status (p=0.028) and family income (p=0,039). The children's average screen time was 2.72 hours/day and that of the parents was 7.37 hours/day. It is concluded that the Parental Media Guidance Scale was translated, adapted and validated for application to parents and/or guardians of children in early childhood. Parents had a predominantly restrictive mediation style. It is noteworthy that, despite the prevalence of more restrictive postures, the same parents also mentioned strategies considered instructive. Portraying that styles are not static within families and that strategies can vary according to the different situations experienced on a daily basis. The results of this study can be used as a guide for nurses' health promotion practices focused on child health, emphasizing the importance of not only transferring the information recommended by reference bodies, but also adjusting such guidelines to the realities of each family, including individualizing the orientation strategies. Therefore, including the mediation of screen time as a relevant guideline for promoting the health of Brazilian families should guide agendas for creating and improving public policies aimed at the well-being of families. Especially with regard to the valuable opportunity to work on public health problems in early childhood, as adjustments for this age group can significantly impact habits that will influence the course of people's lives in the near future.